Housing by people and work - Cavalcanti, Ana Rosa Chagas (A+BE | Architecture and the Built Environment, 2019)
The article takes its roots from a participatory research accomplished by the corresponding author in Brazilian favelas between 2009 and 2017. Ethnographic research, combined with time series analysis and post occupation studies, revealed the everyday practices of residents of informal settlements in Brazil, both in informal settlements and formal housing where residents were eventually resettled. The research proved that labor is the social practice which most of all shapes, plans and governs space of informal settlements. (Cavalcanti, 2017a). The economic activities, which may depend also on the raw materials locally available, morphology of the territory and cultural traditions of the community, are found mainly related to the provision of commerce and service (Cavalcanti, 2017a). These activities take place mostly inside the house, which accommodates both labor and domestic life (Cavalcanti, 2017a; Cavalcanti, 2016). Moreover, also the space outside the house, as well as the design of streets and common spaces are determined by the working activities emplaced by the resident (Cavalcanti, 2017a; Cavalcanti, 2016). In the last years, fast-urbanization is ‘involving mainly middle size cities’ (UN Habitat, 2016). Addressing the spatial dynamics established by inhabitants in informal settlements is becoming of paramount interest for governments and international institutions. In fact, in the time-series analysis phase of the research, it was proved that these social practices are maintained or restored by the resident of informal settlements in the short term also after being transferred into formal social housing with pure domestic function (Cavalcanti, 2018). Inhabitants are moved by contingency to change and mischaracterize the original planning of the formal projects in order to restore the economic activities originally performed in the informal settlements. In fact, interviews in the field revealed that the possibility of performing working activities overrides the right to possess a shelter designed according to principles of formal housing; right in turn paid through the source of income of the inhabitant (Cavalcanti, 2018). On the other hand, besides the legal issues of such a mischaracterization, these modifications often result in an early decay of the hygienic standards initially designed and also in severe structural safety issues, implying a “re-favelization”16 of the social housing (Angelil and Hehl, 2011). This research combines experimental data with the critical analysis of current theoretical and operative approaches in the field of informal settlements’ re-location strategies and processes. This is the approach of the “extended case method,” to “extract the general from the unique […] to connect the present to the past in anticipation of the future […] all building in preexisting theory.” (Burawoy, 1998). The goal of the study is to derive extraordinary theorization in the field of social housing from the ordinary everyday of unprivileged people living in informal settlements. This article presents a new approach of design of social housing for residents of favelas in Brazil based on the integration of space aimed for labor and domestic life. This integration derives from the depiction of social practices which are certainly not new nor limited to current favelas, but rather ancient and rooted in the history of mankind and cities around the world (Arendt, 1958). In many historic-economic contexts characterized by a vocation to commerce and service, the domestic space was still embedded with the production of work (Mumford, 1961). Productive system has also lately determined the development of modern social housing characterized by pure domestic function in industrialized societies (Le Corbusier, 1923; Kenneth Frampton, 1980). Thus, the simple transfer of models of social housing typical of industrialized countries within contexts of the so called “Global South”17, with economy predominantly based on commerce and service, is neither effective nor beneficial for the people and their cities. The critique is not related to the cogent productive systems in the different areas of the world, but rather to the capability of the architect, meant as a political actor of the society, to understand the deep relationship that not only dwelling but rather the concept of space itself establishes with labor in the domain of the city. Thus, the proposal for a new conceptof social housing passes through the critique of the housing methods currently emplaced to relocate residents from informal settlements in the countries of the Global South, both when working activities are prohibited in the house as well as when, as an emerging trend, architects accept or even encourage the modifications emplaced by the future inhabitants to formal housing projects. (Turner, 1976). Both approaches are discussed in the following paragraphs. Instead, the series of operative suggestions proposed in this article for the design of social housing aimed to residents of informal settlements takes roots in the history of mankind meant as a social entity. They restore the integration between labor and domestic life with a triple purpose: an improvement of life condition of the resident; an advancement of his/her socio-economic status; a progress of the economy of the formal city. Thus, apart from the intellectual critique, the content of this article can be operatively beneficial within projects of slum rehabilitation or resettlements processes.